Sesquiterpenoids from the Resina Commiphora Promoting the Apoptotic Activity of PC‐3 Prostate Cancer Cells. Issue 4 (19th April 2023) - Dong, Lu; Li, Yanpeng; Qin, Fuying; Cheng, Yongxian
Abstract: Four new germacrane‐type sesquiterpenes commiphoranes M1‐M4 (1 ‐4 ) together with eighteen sesquiterpenes were isolated from the Resina Commiphora . The structures and relative configurations of new substances were determined by using spectroscopic methods. Biological activity investigation revealed that nine compounds including 7, 9, 14, 16, (+)‐17, (−)‐17, 18, 19, and 20 could induce the apoptosis of prostate cancer originated PC‐3 cells, through classic apoptosis signaling pathway, even using flow cytometry showed that the compound (+)‐17 caused apoptosis of PC‐3 cells more than 40 %, suggesting their potential therapeutic application in the development of novel drugs against prostate cancer. Abstract :